ANALISIS YURIDIS PENYALAHGUNAAN UNMANNED COMBAT AERIAL VEHICLE (COMBAT DRONE) SEBAGAI SENJATA PERANG DITINJAU DARI HUKUM HUMANITER INTERNASIONAL - ROY FALDI ANPRATAMA; Evi Deliana; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The development of the use of weapons technology is currently growingrapidly darting. One of them is the use of technologiUnmanned Aerial Vehicle(UAV) / Drone (aircraft without crew) controlled through a remote control which isused as a weapon into Unmanned Combat Aerial Vehicles (UCAVs) CombatDrones (unmanned aircraft equipped with weapons) which some countries are verymeaningful to minimizing risk in conflict weapon since only be controlled remotelyand claimed can fly up to tens of hours is on one hand very lucrative military field.On the other hand, the impact from the use of these drones should also benoted, because the resulting impact very seriously and according to some legalexperts that the use of armed drones (Combat Drone) violates human rights andlegal humanitarian. One of the example is the impact of such attacks deprive thelives of many people, like the case of the American drone attacks in Pakistan since2004 to 2018 according to the humanitarian agency International bureau ofinvestigates has killed over 4,026 souls therein 2.515- including civilians andchildren due to their use in targeting attacks are indiscriminate.From the results obtained, as the development of weapons such as CombatDrone technology, use of drones as weapons should be formulated in a particularlegal seal the document. Therefore, countries that are currently using dronetechnology should agree to establish the rule of law, so that there is no legal vacuumin the regulation on the use of drones especially relating to its use as a weapon inarmed conflict. The formulation of the rule of law should also pay attention tointernational humanitarian law. Because if not defined, it is very difficult for thestate to define the limits associated used such weapons look very bad impactproduced in the humanitarian field.Keywords: - Drone - Unmanned Combat Drone - Law Enforcement -Internaisonal Humanitarian Law - Legal – Accountability